Quotes from the scientific status of phonetic study - Hammoodi, Hind (Al-Adab Journal, 2025)
Since the Arabic language is a young language, and it has not had a stage in which it has aged, time has passed and it is still fresh and vibrant, and the subject of attention of students and researchers, old and modern, and at all its linguistic levels (phonetics, morphology, grammar, and semantics), meaning the study of phonetics, the first foundation in all languages; the first building block, including the foundation and beginning, the sounds of a specific language are met together to form verbal structures , as the structures that in their meeting on discovery achieve for us what is called (language), what are these sounds that languages ​​depend on? And how can this scientific status be achieved to form a specialized study of it called phonetics? We find the answer to it between the folds of our research article.